Executive Committee Minutes 2005-04-21 - Academic Senate:::::::::
Posthumous Certificate of Recognition for Caitlin Byrd from the Geology dept, Excellence in Teaching Policy revision, Proposed Revised History/Social Sciences Single Subject Preparation Program, Access to Programs for Students with Disabilities Policy, GE FYE resolution from EPC including discussion of facilitating this item at the Senate, Periodic Review of Administrators, Faculty Consultation in Budgetary Matters